Tracing Southern Storytelling in Black and White. - Ford, Sarah Gilbreath, 1968- (University of Alabama Press, 2014)
In Tracing Southern Storytelling in Black and White, Sarah Gilbreath Ford explores how both black and white southern writers such as Joel Chandler Harris, Charles Chesnutt, Zora Neale Hurston, William Faulkner, Eudora Welty, Ralph Ellison, Ellen Douglas, and Ernest Gaines have employed oral storytelling in literature. Tracing Southern Storytelling in Black and White is a study of the historical use of oral storytelling by southern writers in written works. In each chapter, Sarah Gilbreath Ford pairs a white and an African American writer to highlight points of confluence in black and white sout.